Maternal Supply of Ruminally-Protected Lysine and Methionine During Close-Up Period Enhances Immunity and Growth Rate of Neonatal Calves - Wang, Han; Elsaadawy, Samy A.; Wu, Zhaohai; Bu, Dengpan P. (Frontiers in Veterinary Science, 2021)
The objective of this study was to evaluate the effect of supplying ruminally-protected lysine (RPL), methionine (RPM), or the two in combination (RPML) to transition dairy cows on the immunity and performance of their offspring. Eighty heifer calves (n = 20 calves per group) were assigned to four treatments based on their dam diet; basal diet (CON), a basal diet with lysine [RPL, 0.33% of dry matter (DM)], a basal diet with methionine (RPM, 0.16% DM), or with the combination (RPML). Calves were fed colostrum from their dams within 2 h of birth. Calves were then fed milk only (d 2 to 22), a combination of milk and milk replacer (d 23 to 25), and milk replacer (d 25 to 60). Starter feed was fed to the calves twice daily after liquid feeding. Blood samples were collected after calving on 0, 12, 24, and 48 h and 5 and 7 d after birth. Data were analyzed by PROC MIXED of SAS v9.4. Providing ruminally-protected amino acids (RPAA) to transition cows improved colostrum quality compared to the CON (Brix; P < 0.001). Serum total protein concentrations were higher in calves from supplemented cows than in calves from unsupplemented cows (P<0.01). Calves born to dams in the RPM, RPL, and RPML groups had higher plasma immunoglobulin G (IgG) concentrations 0, 12, 24, and 48 h and 7 d after birth than those born to dams in the CON group (P < 0.05). The percentage of calves with adequate passive immunity transfer was increased with RPM and RPL or the two in combination (P < 0.001). However, there was no difference in the percentage of calves with adequate passive immunity transfer between the RPM and RPL groups (P = 0.21). Calves from cows that receive supplemental AA have a greater average daily gain (ADG) than those born to cows in the CON group (P < 0.001). These results indicate that maternal supplementation with RPM or RPL or the two in combination during the periparturient period could be an alternative strategy to improve the performance of calves, especially in accelerated growth programs in calves.